UJI AKTIVITAS EKSTRAK ETANOL KULIT PISANG MAS (Musa acuminata (AA Goup)) TERHADAP PENURUNAN KADAR GLUKOSA DARAH MENCIT (Mus Musculus) YANG DIINDUKSI ALOKSAN - Kadek Evi D.P. Dewi; Abdul Wahid Jamaluddin; Fedri Rell (Fakultas Farmasi UMI, 2018)
Diabetes mellitus (DM) is a metabolic diseases caused by impaired insulin secretion. The prevalence of DM in pets increased from 2006 until 2015.Therapy by using insulin feared can be worse for patient, so yhat alternative medicine is needed like banana peel. The aims of this study isto determine the effect ofethanol extract of Mas banana peel (Musa acuminata (AA Group)) to decrease level of glucose in mice’s blood (Mus musculus) were induced by alloxan. This research was conducted in June 2017 at Biopharmaceutical Laboratory Faculty of Pharmacy, Hasanuddin University. This study uses 24 male mice which divided into 6 groups where the normal control (standard diet), negative control (Na.Cmc 1%), positive control (Metformin 140mg/KgBB) and treatment group by ethanol extract of Mas banana peel 1%, 5%, and 25%. The treatment was given for 10 days. Data were analyzed using one way Anova. The result of this study showed that ethanol extract in banana peel decrease the level of blood glucose which the decrease percentage are 43,15%, 54,61%, 74,28%. The summary of this research is the treatment by using variant concentration of ethanol extract of Mas banana peelfor 10 days give the significant effect for decreasing the level of blood glucose (p<0,05) and the activity of ethanol extract of Mas Banana Peel 25% are not give the significant effect with metformin dose 140mg/KgBB (p>0,05).